Potential Association of DCBLD2 Polymorphisms with Fall Rates of FEV(1) by Aspirin Provocation in Korean Asthmatics - Park, Tae-Joon (The Korean Academy of Medical Sciences, 2012)
Aspirin exacerbated respiratory disease (AERD) is a clinical syndrome characterized by chronic rhinosinusitis with nasal polyposis and aspirin hypersensitivity. The aspirin-induced bronchospasm is mediated by mast cell and eosinophilic inflammation. Recently, it has been reported that the expression of discoidin, CUB and LCCL domain-containing protein 2 (DCBLD2) is up-regulated in lung cancers and is regulated by transcription factor AP-2 alpha (TFAP2A), a component of activator protein-2 (AP-2) that is known to regulate IL-8 production in human lung fibroblasts and epithelial cells. To investigate the associations between AERD and DCBLD2 polymorphisms, 12 common variants were genotyped in 163 AERD subjects and 429 aspirin tolerant asthma (ATA) controls. Among these variants, seven SNPs (rs1371687, rs7615856, rs828621, rs828618, rs828616, rs1062196, and rs8833) and one haplotype (DCBLD2-ht1) show associations with susceptibility to AERD. In further analysis, this study reveals significant associations between the SNPs or haplotypes and the percentage of forced expiratory volume in one second (FEV(1)) decline following aspirin challenge using multiple linear regression analysis. Furthermore, a non-synonymous SNP rs16840208 (Asp723Asn) shows a strong association with FEV(1) decline in AERD patients. Although further studies for the non-synonymous Asp723Asn variation are needed, our findings suggest that DCBLD2 could be related to FEV(1)-related phenotypes in asthmatics.